Implementasi Algoritma Apriori Pada Sistem Prediksi Pemesanan Spanduk Di Percetakan Cipta Aksara 3 Pagaralam - Arif, Alfis (AI Society & STMIK Indonesia, 2022)
The purpose of this study was to implement a Banner Ordering Prediction System Using the Apriori Algorithm at Pagar Alam 3 Pagar Alam Cipta Aksara Printing. At Pagar Alam 3 Pagar Alam Cipta Aksara Printing, a problem was found, namely the difficulty in controlling the available banner-making production materials. When there are banner materials that are often purchased out of stock at the printing press, the printing owner must re-stock the materials and it takes a long time to provide the materials. With the Banner Ordering Prediction System Using the Apriori Algorithm, it was found that the association rules if consumers order 340 ingredients then consumers will order 280 ingredients with a 100% confidence value, if consumers order 280 materials & x-banners then consumers will order 280 ingredients with a confidence value of 100 %, the item if the consumer orders the sticker material, the consumer will order the material 280 with a confidence value of 93.10%, the item if the consumer orders the material 400 then the consumer will order the material 280 with a confidence value of 86.67% and the item if the consumer orders the material 280 then the consumer will order sticker material with a confidence value of 51.92%. With this system, it is hoped that it will simplify the process of providing material for making banners in the future. The system testing method uses Black Box Testing by testing input, output, update, delete, and button functions, with valid (appropriate) results.